Are We Moving Towards Convergence or Divergence? Mapping the Intellectual Structure and Roots of Online Social Network Research 1997–2017. Issue 1 (21st January 2020) - Fu, Jiawei Sophia; Lai, Chih-Hui
Abstract: Online social networks (OSNs), comprised of varying types of relations among actors that interact through social technologies, are widespread in today's media environment. However, questions remain whether we are moving towards convergence within the sub-disciplines of communication and with other disciplines in OSN research. This article pursues two interrelated goals. First, it performs a bibliometric analysis of existing scholarship on OSNs in the past 20 years, highlighting both the convergence and divergence of inquiry on OSNs in computer-mediated communication (CMC) research. Second, based on the results of the bibliometric analysis, it articulates an agenda for future CMC research. Specifically, we advocate for a social network approach that will bridge various theoretical frameworks and disciplinary/sub-disciplinary boundaries, for employing the communication network taxonomy, for greater effort to integrate traditional and computational approaches within and beyond social network analysis, and for addressing a greater diversity of institutional contexts.